Evaluating the presence of IAN injury in patients with juxta-apical radiolucency after third molar surgery: a retrospective cohort study - Mahvash Hasani; Nasim Razavi; Abdolaziz Haghnegahdar; Motahhareh Zarifi (BMC, 2021)
Abstract Background Juxta-apical radiolucency (JAR) has been presented as a radiographic sign, suggestive of the IAN injury through third molar surgery. This study aimed to evaluate the relation of JAR with IAN injury in cone-beam computed tomography (CBCT) images and to determine whether the presence of JAR is related to tooth angulation, proximity to the mandibular canal, position to the IAN, and thinning of the cortical plates. Methods Of an initial sample of 545 mandibular third molars, a total of 75 JAR + and 75 JAR− teeth were evaluated by CBCT. We assessed the relationship between the presence of JAR in cone-beam computed tomography (CBCT) images and the presence of IAN injury after mandibular third molar surgeries. Moreover, we investigated whether the presence of IAN injury is related to tooth angulation, proximity to the mandibular canal, position to the IAN, and thinning of the cortical plates. Descriptive statistics, Chi-square test, and Fisher's exact test were performed for statistical analysis. Results A significant relationship was found between JAR and temporary IAN injury (P = 0.036). However, there was no case of permanent IAN injury. IAN injury showed no significant relationship with the tooth angulation, position to IAN and proximity to the mandibular canal, lingual cortical plate thinning, sex, and age. Conclusions JAR is generally in contact with the mandibular canal, and some degree of cortical thinning can be found in most cases. In this study, JAR was significantly related to temporary IAN injury. JAR may increase the risk of nerve injury during the surgical removal of third molars.